(untitled) (The Research of Medical Science Review, 2025)
Background: In the instance of illness, there are various difficulties that Afghan refugee women have to encounter them to get the necessary treatment. There is cultural stigma, economic factors, and most importantly, the distressing factor of being in displacement, which are a few of the challenges women grapple with. This study examines the health-seeking behaviors of Afghan women in the suburbs of Islamabad, with a particular focus on the H-11 community. This helps to draw attention to specific challenges in the given locality. Objectives: To evaluate the healthcare services available to Afghan refugee women in suburban Islamabad. To identify the cultural, social, and economic barriers that prevent access to healthcare. To recommend policy interventions to improve healthcare access for Afghan refugee women. Methods: Semi-structured interviews involving open-ended questions were utilized with each of the twelve Afghan refugee women. These women were categorized depending on their life cycle stages: girl child, adolescent girls, reproductive age, and post-reproductive age, also referred to as menopausal. Consequently, a thematic analysis was conducted for the purpose of identifying the main aspects that shape the decisions regarding healthcare. Results: Based on the interpretation of the results, it was learned that people's way of seeking care was influenced by their sociocultural norms, especially those pertaining to gender and their traditional medicine practices. Many of the young unmarried women, as well as others, would often turn to traditional healers when they could not pay for formal treatment. Language barriers in Islamabad H-11 were especially significant. Conclusion: Both groups have challenges in getting overcome by healthcare systems, mainly due to a relationship with culture as well as economic factors. Instead, culturally suitable healthcare solutions and an increase in the coverage of healthcare services for refugees should be the driving force of reform among policymakers.